2017
DOI: 10.1002/2016jg003755
|View full text |Cite
|
Sign up to set email alerts
|

Winter climate change and fine root biogenic silica in sugar maple trees (Acer saccharum): Implications for silica in the Anthropocene

Abstract: Winter temperatures are projected to increase over the next century, leading to reductions in winter snowpack and increased frequency of soil freezing in many northern forest ecosystems. Here we examine biogenic silica (BSi) concentrations in sugar maple (Acer saccharum) fine roots collected from a snow manipulation experiment at Hubbard Brook Experimental Forest (New Hampshire, USA). Increased soil freezing significantly lowered the BSi content of sugar maple fine roots potentially decreasing their capacity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The extent to which plants can actively control Si accumulation relative to passive uptake that is hydraulically and osmotically driven is still debated (Kumar, Milstein, Brami, Elbaum, & Elbaum, 2017;McLarnon, McQueen-Mason, Lenk, & Hartley, 2017;Quigley & Anderson, 2014). There is, however, wider recognition that climatic factors such as water availability and temperature influence Si accumulation (Hartley, 2015;Maguire, Templer, Battles, & Fulweiler, 2017;Schoelynck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which plants can actively control Si accumulation relative to passive uptake that is hydraulically and osmotically driven is still debated (Kumar, Milstein, Brami, Elbaum, & Elbaum, 2017;McLarnon, McQueen-Mason, Lenk, & Hartley, 2017;Quigley & Anderson, 2014). There is, however, wider recognition that climatic factors such as water availability and temperature influence Si accumulation (Hartley, 2015;Maguire, Templer, Battles, & Fulweiler, 2017;Schoelynck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Transpiration‐based estimates exceed those in litter by twofold to fivefold, although Si is largely immobile in live foliage, with minimal leaching (Markewitz & Richter, ). Any accumulation in root tissue (i.e., as observed by Maguire et al, ) would presumably happen before we sampled the transpiration stream in branches, as Si is not known to be relocated in the phloem (Exley, ). We conclude that some sequestration in wood (e.g., Clymans et al, ) combined with measurement uncertainty may explain this observation.…”
Section: Discussionmentioning
confidence: 98%
“…Belowground sequestration is also challenging to measure, and elemental concentrations are rarely reported, although may be important in some cases. Maguire et al (), for example, estimated that 29% of biogenic Si in A. saccharum is present in fine roots, which account for less than 4% of the tree biomass. Using green leaves to estimate litter flux, as we did here, does not account for any resorption that may occur during senescence (Vergutz et al, ), potentially overestimating return to the soil surface.…”
Section: Discussionmentioning
confidence: 99%
“…These small-scale phytogenic Si were demonstrated to influence various soil and plant processes (Meunier et al, 2017;Puppe et al, 2017). Maguire et al (2017), who examined the impact of climate change on Si uptake by trees, observed that fine roots of sugar maple (Acer saccharum), which represented only 4 % of the tree's biomass, accumulated 29 % of the Si.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high Si content of fine roots (Krieger et al, 2017;Maguire et al, 2017) and their rapid turnover in forest ecosystems (approximately 1 year in beech forests in Europe; Brunner et al, 2013), we hypothesized that fine roots could significantly contribute to the input of BSi into the soil.…”
Section: Introductionmentioning
confidence: 99%